KUALITAS PELAYANAN PENDIDIKAN DASAR DI SD INPRES KOLONGAN KECAMATAN KOMBI KABUPATEN MINAHASA - TANOD, LITHA MARIA; LALOMA, ALDEN; LONDA, VERY (Sam Ratulangi University, 2018)
Education is one of the areas that get serious attention from the government, because education isone important aspect in national development, without any definite education the state will not have thelevel of competition in the international world. Teachers as educators contain a very broad meaning, notlimited to providing teaching materials, but to reach ethics and aesthetic behavior in facing the challengesof life in society. As teachers, teachers should have a mature teaching plan. Teaching planning is closelyrelated to various elements such as teaching objectives, teaching materials, learning activities, teachingmethods, and evaluation. With creativity and competence, besides mastering the material and can processthe learning program, teachers are also required to carry out evaluation and administration. The ability ofteachers to develop the learning process and their mastery of teaching materials is not enough. The abilityof teachers in mastering the class is balanced with the ability to evaluate the students' competency planningthat is crucial in the context of the next planning, or policy of treatment of students related to the conceptof complete learning. The method used in this research is qualitative research method. Through educationis expected to improve the dignity of Indonesian society both nationally and internationally. Quality ofservice is a dynamic state that is closely related to products, services, human resources, and processes andenvironments that at least can meet or even exceed the quality of service expected. This study aims todetermine how the quality of education services in Elementary School (SD) Inpres Kolongan District KombiMinahasa District. The result of the research shows that the quality of service in SD Inpres Kolongan is stillless good because of the lack of supervision from the headmaster in this case the principal, the lack offacilities and infrastructure, the lack of assertiveness of the principal headmaster in giving disciplinarysanction to teachers who often come late or not timely in terms of attendance at school and lack ofprofessional skills of teachers such as lack of mastery of the field of study in the school curriculum. Toimprove the quality of education services in SD Inpres Kolongan, the researcher suggests that supervisionfrom the head of the school principal should be improved, it is also expected that the provision of supportingfacilities and infrastructures must be sanctioned by the leader to the teachers who often come late andexpected to be coached and training to the principals and teachers in order to improve the quality of teachersin carrying out duties and responsibilities and can better master the teaching materials or schoolcurriculum.Keywords: service quality